1995
DOI: 10.1128/jb.177.19.5644-5652.1995
|View full text |Cite
|
Sign up to set email alerts
|

Purification, characterization, and genetic analysis of Mycobacterium tuberculosis urease, a potentially critical determinant of host-pathogen interaction

Abstract: Mycobacterium tuberculosis urease (urea amidohydrolase [EC 3.5.1.5]) was purified and shown to contain three subunits: two small subunits, each approximately 11,000 Da, and a large subunit of 62,000 Da. The N-terminal sequences of the three subunits were homologous to those of the A, B, and C subunits, respectively, of other bacterial ureases. M. tuberculosis urease was specific for urea, with a K m of 0.3 mM, and did not hydrolyze thiourea, hydroxyurea, arginine, or asparagine. The enzyme was active over a br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
81
0
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 39 publications
1
81
0
2
Order By: Relevance
“…Indeed, previous results have shown that at least gelatinase (Imboden et al, 1996), fibrinogen and elastin hydrolase (Dave et al, 1996), urease (Clemens et al, 1995) or phospholipase (Wheeler & Ratledge, 1992) activities can be induced or strongly stimulated according to the culture medium. Cultivating the micro-organisms on media containing various substrates mimicking the environment of infected cells would complement the present approach.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous results have shown that at least gelatinase (Imboden et al, 1996), fibrinogen and elastin hydrolase (Dave et al, 1996), urease (Clemens et al, 1995) or phospholipase (Wheeler & Ratledge, 1992) activities can be induced or strongly stimulated according to the culture medium. Cultivating the micro-organisms on media containing various substrates mimicking the environment of infected cells would complement the present approach.…”
Section: Discussionmentioning
confidence: 99%
“…ureC is involved in the maintenance of neutral intraphagosomal pH within BCG-containing vacuoles (21). Hence, lack of this enzyme allows phagosomal acidification, thereby creating an optimal pH milieu for cytolytic functions of Hly.…”
Section: Figurementioning
confidence: 99%
“…Latex beads were coated with urease from Bacillus, which is closely related to mycobacterial urease (9). Beads were washed twice with 25 mM morpholineethanesulfonic acid buffer (pH 5.5), and pellets were resuspended in the same buffer containing 500 g of either Bacillus pasteuri urease (ϳ200 U/mg of protein; Sigma) or bovine serum albumin (BSA; control)/ml.…”
Section: Reagentsmentioning
confidence: 99%